Ligand-Free Palladium-Catalyzed Substoichiometric Base Mediated Carbonylation of Aryl Iodides with Alkenylboronic Acids under Ambient Conditions - Tang, Lili; Gao, Yanqun; Chen, Junjie; Yang, Linlin; Xiao, Bing; Shen, Ge; Ouyang, Yuejun; Han, Wei (Synlett, 2023)
A highly efficient, practical, and ligand-free palladium-catalyzed carbonylation of aryl iodides with alkenylboronic acids has been developed. A variety of chalcones and α-branched enones were isolated in satisfactory to good yields with good substrate compatibilities under an ambient pressure of CO at room temperature. Moreover, the transformation proceeds well in the presence of a substoichiometric amount of base. The merit of this strategy as a late-stage functionalization platform has been demonstrated by modifications of complex substrates derived from estrone and 3-phenyl-l-alanine.
Keywords: palladium catalysis; carbonylation; aryl iodides; alkenylboronic acids; chalcones; enones